2008
DOI: 10.1002/cncr.23650
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary diffuse gastric cancer

Abstract: Approximately 10% of patients with gastric cancer show familial clustering, and 3% show autosomal dominance and high penetrance. Hereditary diffuse gastric cancer (HDGC) is an autosomal-dominant, inherited cancer syndrome in which affected individuals develop diffuse-type gastric cancer at a young age. Inactivating mutations in the E-cadherin gene CDH1 have been identified in 30% to 50% of patients. CDH1 mutation carriers have an approximately 70% lifetime risk of developing DGC, and affected women carry an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(18 citation statements)
references
References 45 publications
1
15
0
2
Order By: Relevance
“…HDGC is an autosomal-dominant inherent cancer syndrome, and approximately 30% of individuals with a clinical diagnosis of HDGC harbor germline mutation of CDH1 [31,32]. Among individuals with CDH1 germline mutations, the cumulative risk of advanced gastric cancer by age 80 years is 69% in men and 83% in women [33].…”
Section: Hereditary Diffuse Gastric Cancermentioning
confidence: 99%
“…HDGC is an autosomal-dominant inherent cancer syndrome, and approximately 30% of individuals with a clinical diagnosis of HDGC harbor germline mutation of CDH1 [31,32]. Among individuals with CDH1 germline mutations, the cumulative risk of advanced gastric cancer by age 80 years is 69% in men and 83% in women [33].…”
Section: Hereditary Diffuse Gastric Cancermentioning
confidence: 99%
“…Alternatively, it has been suggested that total gastrectomy should be considered in CDH1 mutation carriers at an age five years younger than the youngest family member who developed gastric cancer [69].…”
Section: Managementmentioning
confidence: 99%
“…HDGC is a subgroup of diffuse gastric cancer 22. The average age of onset of HDGC is 38 years, and the CDH1 gene mutation is the only genetic mutation described so far that has been associated with the occurrence of HDGC (25%~50% of cases) 23.…”
Section: Discussionmentioning
confidence: 99%